Corrigendum to “Recycling of crustal material by the Iceland mantle plume: New evidence from nitrogen elemental and isotope systematics of subglacial basalts” [Geochim. Cosmochim. Acta 176 (2016) 206–226] - Halldórsson, S; Hilton, D; Barry, P; Füri, E; Grönvold, K (Elsevier, 2016)
In Table 1 of the above published paper, N2/40Ar* ratios (column 13) are incorrect. A corrected table and updated figures (Figs. 6–8) are shown below. The correct N2/40Ar* values vary between 178 and 2.6 X 10^4, with a mean of 4.1 ± 2.1 (X10^3). Although this range in N2/40Ar* ratios is somewhat smaller compared to what was reported, it still displays considerably more heterogeneity compared to the DMM database. The new mean value is also significantly higher than the DMM mean (138 ± 65), as discussed. Therefore, the findings in the paper concerning heterogeneous and elevated N2/40Ar* ratios in Icelandic subglacial basalts still stand.